2013
DOI: 10.2106/jbjs.l.00759
|View full text |Cite
|
Sign up to set email alerts
|

Operative Versus Nonoperative Treatment of Displaced Intra-Articular Calcaneal Fractures

Abstract: Therapeutic level II. See instructions for authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
149
1
9

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(162 citation statements)
references
References 29 publications
3
149
1
9
Order By: Relevance
“…This may be due to weight bearing after one and a half month, proper immobilization for the required time or due to good compliance of patients. The outcomes in both conservative and operative groups in this study are comparable with all other (Griffin, 12 Argen, 13 Buckley 5 ) studies (Table 7).…”
Section: [ ( F I G _ 1 ) T D $ F I G ]supporting
confidence: 87%
“…This may be due to weight bearing after one and a half month, proper immobilization for the required time or due to good compliance of patients. The outcomes in both conservative and operative groups in this study are comparable with all other (Griffin, 12 Argen, 13 Buckley 5 ) studies (Table 7).…”
Section: [ ( F I G _ 1 ) T D $ F I G ]supporting
confidence: 87%
“…Jiang et al 18 in their meta-analysis had reported better results with operative management but observed higher complication rate. Agren et al 19 in their multicentric, prospective, randomised trial had reported similar functional outcomes in displaced intraarticular calcaneal fractures, whether treated operatively or non-operatively. However, at eight-to twelve-year follow-up, better pain scores, functional outcome and lower incidence of post-traumatic subtalar arthritis were seen in operatively treated group.…”
Section: Discussionmentioning
confidence: 91%
“…In our study group, postoperative infection was found in 7% of the cases, but almost 6% were superficial in fections treated without secondary complications. A similar study was conducted by surgeons from Sweden and Canada [25,26]. Despite the fact that there were no statistically significant differences between operative and conservative treatment, the authors of one study opt for surgery while the other team recommends con servative treatment.…”
Section: Discussionmentioning
confidence: 93%
“…W na szej gru pie cho rych do za ka że nia po opera cyj ne go do szło w 7% przy pad ków, z cze go pra wie 6% sta no wi ły za ka że nia po wierz chow ne wy le czo ne bez wtór nych po wi kłań. Po dob ne ba da nie zo sta ło prze pro wa dzo ne przez chi rur gów ze Szwe cji i Ka nady [25,26]. Mi mo bra ku zna czą cych sta ty stycz nie ró żnic mię dzy le cze niem ope ra cyj nym i nie ope ra cyjnym, jed ni z nich opo wia da ją się za wy ższo ścią opera cji, dru dzy -za le cze niem za cho waw czym.…”
Section: Dys Ku Sjaunclassified